2012
DOI: 10.1093/nar/gks1096
|View full text |Cite
|
Sign up to set email alerts
|

A complex network framework for unbiased statistical analyses of DNA–DNA contact maps

Abstract: Experimental techniques for the investigation of three-dimensional (3D) genome organization are being developed at a fast pace. Currently, the associated computational methods are mostly specific to the individual experimental approach. Here we present a general statistical framework that is widely applicable to the analysis of genomic contact maps, irrespective of the data acquisition and normalization processes. Within this framework DNA–DNA contact data are represented as a complex network, for which a broa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 48 publications
9
31
0
Order By: Relevance
“…Then, using active transcription, Pol II would distribute cohesin on chromosomes, extruding DNA in the process to form loops and TADs (Busslinger et al 2017). This model is corroborated by other network analyses suggesting a primary role for active Pol II and cohesin in the formation of chromatin-chromatin interactions (Kruse et al 2013;Pancaldi et al 2016;Azofeifa and Dowell 2017). Interestingly, NIPBL seems to favor promoter-promoter interactions (Pancaldi et al 2016).…”
Section: Discussionsupporting
confidence: 60%
“…Then, using active transcription, Pol II would distribute cohesin on chromosomes, extruding DNA in the process to form loops and TADs (Busslinger et al 2017). This model is corroborated by other network analyses suggesting a primary role for active Pol II and cohesin in the formation of chromatin-chromatin interactions (Kruse et al 2013;Pancaldi et al 2016;Azofeifa and Dowell 2017). Interestingly, NIPBL seems to favor promoter-promoter interactions (Pancaldi et al 2016).…”
Section: Discussionsupporting
confidence: 60%
“…CUFS correlates better with 3DGD than the genes' GC content. In SC, GC content was reported to be correlated with recombination frequency 47 , while crossover recombination sites were reported to be enriched in Hi-C contacts 20 . In addition, centromeres have been reported to be strongly co-localized 12 , and have also been characterized as having low GC content 48 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, recently a correlation has been suggested between transcription factor network models and distances between average chromosome positions in human cells 19 . A series of studies further reported the co-localization of each of the following groups in SC: cohesin binding sites 20 , co-expressed genes, some identified GO terms 21 and gene targets of the same transcription factor 22 . Recently, an analysis of the genomic organization of the unique P. falciparum parasite throughout its cell cycle confirmed a relation between chromosome conformation and gene expression 18 .…”
mentioning
confidence: 99%
“…Although some studies about the analysis of long-range interaction networks have been presented [34,35], current approaches to Hi-C data analysis mostly rely on the conversion of information into contact maps, which are matrices of pair wise contact frequencies along the genome. Also data normalization is performed directly on the contact maps, with the aim of filtering out biases caused by fragment length, mappability, and GC-content.…”
Section: Introductionmentioning
confidence: 99%